Effect of Tax System on the Economic Development of a Nation: Nigeria Experience - Olalekan Oladipo, Akinrinola; Bamidele, Oreoluwa (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The economic development of Nigeria has been trembling over the years, even when the country has been acclaimed the biggest economy in Africa since 2014. This is in contrast to other developing countries and sub-Saharan countries that have up-scaled and accelerated their economic development in contemporary times. Such nations have utilised tax revenue to galvanise their economic development, but Nigeria does not have much to show for this. The country records one of the lowest percentage of tax revenue to GDP of about 6% compared to an average of 17% for sub-Saharan African countries and about 30% for OECD countries. This study examined the effect of the tax system on the economic development of the nation, using the human development index as the parameter for measuring economic development while assessing the tax system by the tax to GDP ratio. A qualitative research method was adopted by reviewing empirical studies and analysing secondary data gathered from relevant sources. From the reviews, discussions and analysis, there abounds compelling data to show that there is significant positive relationship between the tax system and the economic development of a nation. However, in the case of Nigeria, there appears to be uncoordinated and ineffective tax system that has inadequately impacted on her economic development. Taking a lead from other developing countries like Rwanda, recommendations were made for restructuring and synergising the tax system while utilizing information technology and ensuring accountability and transparency.